Emerging waste-to-wealth applications of fly ash for environmental remediation: A review - Hong-Ha T. Nguyen, Hong-Ha T. Nguyen; Ha Tran Nguyen, Ha Tran Nguyen; Shams Forruque Ahmed, Shams Forruque Ahmed; Natarajan Rajamohan, Natarajan Rajamohan; Mohammad Yusuf, Mohammad Yusuf; Ajit Sharma, Ajit Sharma; Priya Arunkumar, Priya Arunkumar; Balakrishnan Deepanraj, Balakrishnan Deepanraj; Huu-Tuan Tran, Huu-Tuan Tran; Adel Al-Gheethi, Adel Al-Gheethi; Dai-Viet N. Vo, Dai-Viet N. Vo (Elsevier, 2023)
The considerable increase in world energy consumption owing to rising global population, intercontinental transportation and industrialization has posed numerous environmental concerns. Particularly, in order to meet the required electricity supply, thermal power plants for electricity generation are widely used in many countries. However, an annually excessive quantity of waste fly ash up to 1 billion tones was globally discarded from the combustion of various carbon-containing feedstocks in thermoelectricity plants. About half of the industrially generated fly ash is dumped into landfills and hence causing soil and water contamination. Nonetheless, fly ash still contains many valuable components and possesses outstanding physicochemical properties. Utilizing waste fly ash for producing value-added products has gained significant interests. Therefore, in this work, we reviewed the current implementation of fly ash-derived materials, namely, zeolite and geopolymer as efficient adsorbents for the environmental treatment of flue gas and polluted water. Additionally, the usage of fly ash as a catalyst support for the photodegradation of organic pollutants and reforming processes for the corresponding wastewater remediation and H2 energy generation is thoroughly covered. In comparison with conventional carbonbased adsorbents, fly ash-derived geopolymer and zeolite materials reportedly exhibited greater heavy metal ions removal and reached the maximum adsorption capacity of about 150 mg g− 1 As a support for biogas reforming process, fly ash could enhance the activity of Ni catalyst with 96% and 97% of CO2 and CH4 conversions, respectively.